Hydrogeological assessment of groundwater resources in Khutti Khola Watershed, Siraha District, Eastern Nepal - Khadka, Goma; Dhungana, Sumitra; Acharya, Manjari; Sah, Ram Bahadur; Paudyal, Kabi Raj (Journal of Nepal Hydrogeological Association, 2024)
The Khutti Khola watershed, located in eastern Nepal, is a region that has been experiencing increasing water scarcity over the past few decades. These regions face water scarcity due to rapid and poorly planned urbanization, fragile geology, overexploitation of existing water resources and ineffective water governance systems. The present study focuses on examining the availability, distribution, and management of groundwater resources in Khutti Khola watershed. It provides insights into the geological features, hydrogeological inventories, water table dynamics of Khutti Khola watershed and a Nature-based Solution (NbS) for groundwater recharge at water scarce areas of Bhabar zone. Hydrogeological assessment was carried out in Terai, Bhabar as well as Chure region within Khutti Khola watershed and the local people from the communities were interviewed for the identification of water scarce areas. The main scarcity was found in places like Ranaha, Dadatol and Simaltoki in the Bhabar zone. Recommendations for the development of artificial ponds were proposed in those areas as a Nature-based Solution (NbS) and a feasibility study was carried out for identifying the appropriate location for the pond. As such ponds made at the surface of the recharge zone will work as extra pockets to store surface runoff and recharge the area, construction of artificial recharge pond is recommended as sustainable solutions to mitigate water scarcity in the Khutti Khola watershed and similar regions across Nepal, ultimately improving livelihoods and resilience of local communities.